Experts at Being Novices: What New Teachers Can Add to Practice-based Teacher Education Efforts. (2nd July 2020) - Peercy, Megan Madigan; Kidwell, Tabitha; Lawyer, Megan DeStefano; Tigert, Johanna; Fredricks, Daisy; Feagin, Karen; Stump, Megan
ABSTRACT: Understood as one approach to enacting a practice-based pedagogy of teacher education, core practices (CPs) have in the last decade become part of the discussion in general teacher education, and within particular content areas. CPs are viewed as practices that are essential to student learning and critical to novice teachers' (NTs') early career success. However, while these pedagogies may serve as an important scaffold to NT learning, their impact on NT practice is still mostly unknown, and efforts to develop practice-based pedagogies have largely been led by researchers, with little direct involvement by PK-12 practitioners. In this paper, we argue that more intentional and purposeful involvement of NTs in the development, selection, and refinement of CPs generates greater potential to support NT practice. Drawing upon observations of NT practice, interviews, and transcripts from meetings of our collaborative team of NTs and teacher educators, we illustrate how engaging NTs as knower-learners can contribute to the development of more responsive pedagogies of teacher education.